A Series of Rare‐Earth Mesoionic Carbene Complexes. Issue 37 (23rd May 2022) - Seed, John A.; Vondung, Lisa; Barton, Franky; Wooles, Ashley J.; Lu, Erli; Gregson, Matthew; Adams, Ralph W.; Liddle, Stephen T.
Abstract: We report the synthesis and characterisation of a series of rare‐earth mesoionic carbene complexes, [REN(SiMe3 )2 3 CN(Me)C(Me)N(Me)CH] (3RE, RE=Sc, Ce, Pr, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu), greatly expanding the limited library of f‐block mesoionic carbene complexes. These complexes were prepared by treatment of the parent RE‐triamides with an N ‐heterocyclic olefin (NHO), where an NHO backbone proton undergoes a formal 1, 4‐proton migration to the NHO‐methylene group. For all RE(III) metals, as expected, quantum chemical calculations suggest only a σ‐component to the metal−carbene bonding, in contrast to a previously reported uranium(III) congener where the 5f 3 metal engages in a weak π‐back‐bond to the MIC. All complexes were characterised by static variable‐temperature magnetic measurements, and dynamic magnetic measurements reveal that 3Dy and 3Er are field‐induced single‐molecule magnets (SMMs), with U eff energy barriers of 35 and 128 K, respectively. Complex 3Dy is, as expected, a poorly performing SMM, but conversely 3Er performs unexpectedly well. Abstract : The generality of employing N ‐heterocyclic olefins in the synthesis of mesoionic carbene (MIC) complexes has been shown here with the advent of twelve new f‐block and rare‐earth metal MIC complexes, expanding the library of f‐block and rare‐earth MIC complexes from four to now sixteen in total. Structural, spectroscopic, and computational characterisation data suggest the presence of a solely σ‐component to the M−Ccarbene bonding interaction, whilst magnetic studies highlight that two of the MIC complexes are field‐induced single molecule magnets (SMMs).